Do Ecopassages Affect Daily Movements and Home Ranges of Blanding's Turtles (Emydoidea blandingii)? - O'Halloran, Andrea (Université d'Ottawa / University of Ottawa, 2024)
Global biodiversity has been decreasing at an alarming rate due to factors such as over-exploitation of species, habitat loss, and fragmentation. A major contributor to habitat loss and fragmentation is road development. Massive road networks span our landscapes and contribute to loss of biodiversity in many ways, such as road mortality. Mitigation techniques, such as ecopassages and exclusion fencing, are implemented across the world to reduce road mortality, though few studies have explored their effectiveness at maintaining movement. Within the Canadian Nuclear Laboratories (CNL) in Chalk River, Ontario, Canada, there is a small population of Blanding's turtles (Emydoidea blandingii), a federally protected species. In 2014/15, a radiotelemetry study was conducted to assess habitat use and movement patterns of this species at CNL. Seven ecopassages and exclusion fencing were installed along the main access roads following this study. I wished to determine whether the installation of ecopassages at CNL has improved habitat connectivity and spatial distribution of Blanding's turtles. Thus, I repeated the radiotelemetry study after the installation of the ecopassages. Movement patterns and home ranges were not significantly impacted by ecopassage presence, however, population spatial distribution decreased after ecopassage installation. Considering the widespread use of ecopassages by animals, these findings highlight the need for further investigation into the effectiveness of ecopassages for reptiles prior to continued application of this road mitigation strategy.
Keywords: Road Ecology; Management; Species at risk; Home Range; Reptile; Mitigation Solutions; Wildlife Passages; Blanding's Turtles; Movement